Comparing Low-Dose Carvedilol Continuous Manufacturing by Solid and Liquid Feeding in Self-Emulsifying Delivery Systems via Hot Melt EXtrusion (SEDEX) - Ožbej Zupančič; Josip Matić; Aygün Doğan; Alessio Gaggero; Johannes Khinast; Amrit Paudel (MDPI AG, 2024)
Background/Objectives: This study compared two pilot scale continuous manufacturing methods of solid self-emulsifying drug delivery systems (SEDDSs) via hot melt extrusion (HME). Methods: A model poorly water-soluble drug carvedilol in low dose (0.5-1.0% w/w) was processed in HME either in a conventional powder form or pre-dissolved in the liquid SEDDS. Results: HME yielded a processable final product with up to 20% w/w SEDDS. Addition of carvedilol powder resulted in a non-homogeneous drug distribution in the extrudates, whereas a homogeneous drug distribution was observed in pre-dissolved carvedilol. SEDDSs were shown to have a plasticizing effect, reducing the HME process torque up to 50%. Compatibility between excipients and carvedilol in the studied ratios after HME was confirmed via DSC and WAXS, demonstrating their amorphous form. Solid SEDDSs with Kollidon® VA64 self-emulsified in aqueous medium within 15 min with mean droplet sizes 150-200 nm and were independent of the medium temperature, whereas reconstitution of Soluplus® took over 60 min and mean droplet size increased 2-fold from 70 nm to 150 nm after temperature increased from 25 °C to 37 °C, indicating emulsion phase inversion at cloud point. Conclusions: In conclusion, using Kollidon® VA64 and pre-dissolved carvedilol in SEDDS has shown to yield a stabile HME process with a homogenous carvedilol content in the extrudate.